Effects of Pacific Intertropical Convergence Zone precipitation bias on ENSO phase transition - Yoo-Geun Ham; Jong-Seong Kug (Environmental Research Letters, 2014)
In this study, the effect of mean precipitation bias over the Pacific Intertropical Convergence Zone (ITCZ) on the El Niño southern oscillation (ENSO) transition is examined using CMIP3 and CMIP5 archives. It is found that the climate models with excessive mean precipitation over the central/eastern Pacific ITCZ tend to simulate slower phase transition of the ENSO. This is because a wetter climatology provides a favorable condition for anomalously strong convective activity; the El Niño-related convection anomaly tends to be increased over the central/eastern Pacific ITCZ with a local wet bias. This induces additional low-level westerlies over the central/eastern equatorial Pacific. As a result, the ENSO-related zonal wind stress anomaly over the central Pacific, which is south of the equator without the wet ITCZ bias during boreal winter, is shifted to the east, and its meridional width is expanded northward. It is found that both the eastward shift and northward expansion of ENSO-related wind stress can lead to slower ENSO phase transition as it takes longer time for the reflected Rossby waves to suppress the ENSO growth. This implies that the off-equatorial mean precipitation plays an important role in ENSO phase transition.